Insidensi Penyakit Karat (Puccinia arachidis) pada Tanaman Kacang Tanah (Arachis hypogaea L.) di Kecamatan Tompaso Dan Kawangkoan Kabupaten Minahasa - Ridwan Aneta; Max M Ratulangi; Guntur S.J. Manengkey (COCOS, 2016)
SUMMARYDisease Incidence Rust (Puccinia arachidis) on plants of Peanut (Arachis hypogaea L.) in District Tompaso and Kawangkoan MinahasaRidwan Aneta, Max M. Ratulangi, and Guntur S. J. ManengkeyThe purpose and benefits of the research to determine the incidence of rust on peanut plants in the District Tompaso and Kawangkoan Minahasa, and the benefits of research can provide information to the relevant agencies, especially to farmers about the existence of this disease in order to prepare a peanut crop control strategies of the disease. The research was conducted in three village namely Pinabetengan, Kanonang and Kayuuwi, District Kawangkoan, Minahasa, and the study lasted for four months. The results showed that the symptoms ofdisease-causing pathogen attack or rust fungus Puccinia arachidis on peanut plants occur at all levels of the age of the plant is vegetative and generative growth. Pathogens forming patches on the surface of the lower and upper leaves with urediospora there are more obvious on the lower leaf surface than the upper surface of the leaf. The results of microscopic observation showed that urediospora shaped somewhat oval, urediospora with brownish colored water media while the media Laktofenol Cotoon Blue color changes such as a golden brown. Furthermore, the incidence of fungi that cause rust on peanut plants are in the village Kayuuwi lowest with an average percentage of 17.75; The village following Pinabetengan with an average percentage of 19.75; and was highest in the Village Kanonang with an average percentage of 22.67. Furthermore the average overall incidence is 20,06 %Keyword: Peanut, Rust Diseases Puccinia arachidis